Somatotype and kinanthropometric characteristic of male and female junior and elite senior alpine skiers - Taeymans, J.; Aerenhouts, D.; Clijsen, R.; Fässler, R.; Clarys, P.; Baeyens, J. P. (Book of Abstracts. 5th International Congress on Science and Skiing, Dec. 14 - 19, 2010, St. Christoph am Arlberg, 2010)
INTRODUCTION: This ongoing study aims to describe the specific somatotype and physical characteristics in junior (J) and senior (S) male and female elite alpine skiers.